Membangun Gerakan Moderasi Beragama Melalui Seni Pertunjukan - Arimbawa, I Komang Suastika (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Exclusive religious viewpoints and attitudes will ultimately give birth to various destructive practices in the form of religious intolerance and violence. This cannot be allowed to continue to grow and develop. This is the sacred duty of every component of the nation. Arts education institutions or arts groups can take a role in efforts to realize the principle of moderation in religion in order to safeguard and maintain the integrity of the nation, by conducting studies, socializing and internalizing the principle of moderation so that it can give birth to education. education. a big movement called the movement for religious moderation through the medium of performing arts. The religious moderation movement stems from (1) the development of extreme religious views, attitudes and practices, (2) the development of subjective truth claims and coercion of will over religious interpretations, and (3) the development of religious enthusiasm that is not in accordance with religion. according to religion. in line with national love within the framework of the Unitary State of the Republic of Indonesia. A responsive attitude towards the phenomenon of social change will ultimately be able to produce 'renewal'. The renewal here is not a religious renewal, but rather an intellectual tradition. Where intellectual traditions are usually dynamic, creative and innovative so that religion becomes lasting and actively provides solutions to various life problems. This is where art can be an effective catalyst in the movement for religious moderation. Universal art can provide space to foster religious moderation. The existence of art from various Indonesian cultures should be able to play a role in developing and maintaining a moderate attitude as a glue and unifier of the nation.